The Absorption and Electrolysis of Hydrogen Sulphide in a Recirculated Alkaline Liquor Containing the Vanadium (IV/V) Redox Couple - Prosser, David (My University, 1985)
The vanadium mediated electrolysis of hydrogen sulphide has been demonstrated in a bench top pilot plant. The first step in the process is the absorption of hydrogen sulphide from a sour gas stream into an carbonate buffered liquor, pH 9. In the presence of citrate ion, the vanadium (V) in the liquor is reduced to vanadium (IV) by (hydro) sulphide ion, which is oxidized to yellow elemental sulphur. The vanadium (IV) rich solution is then pumped to an electrolysis cell where the vanadium (IV) is reoxidized to vanadium (V) and protons are reduced to elemental hydrogen. The reoxidized liquor is then returned to the absorber. The oxidation of vanadium (IV) to vanadium (V) in the liquor was found to be electrochemically irreversible. The current efficiency for vanadium (IV) oxidation exceeded 90 percent. The voltametric half-wave potential at platinum, was 0.34 v (vs Ag/AgCl, sat. KC1). With the slippage of sulphide or polysulphide ion into the electrolysis cells, the electrodes became passivated with electrodeposited sulphur. This resulted in an increased anode potential demand which may promote the electrosynthesis of oxygen and sulphate ion. The oxidation of vanadium (IV) at the anode releases 4 protons and acidifies the solution adjacent the electrode surface. This may induce carbon dioxide evolution and inhibit the discharge of vanadium (IV). The inhibition appears as a suppressed current and an anodic shift in the voltametric half-wave potential. This inhibition can be minimized at high pH levels in the liquor, buffer capacity., and citrate concentration. The irreversibility of the vanadium (IV/V) couple allows electrolysis cells to be constructed without a cell membrane. This is a significant advantage which will offset the cost of large electrolysis cells. Large cells will enable high energy efficiencies to hydrogen production to be realized. Energy efficiencies greater than 0.28 m3 /kwhr may be indicated. This study features a critical review of sulphide electro-oxidation, a factorial designed voltametric experiment, and a newly identified catalytic response in the polarographic analysis of sulphide ion.
This thesis is missing page 89, no other copy of the thesis has this page. -Digitization Centre
Keywords: absorption; electrolysis; hydrogen sulphide; recirculated alkaline liquor; vanadium